Expression of combinatorial immunoglobulins in macrophages in the tumor microenvironment. - Tina Fuchs; Martin Hahn; Lukas Ries; Sophie Giesler; Svenja Busch; Chunlin Wang; Jian Han; Torsten J Schulze; Kerstin Puellmann; Alexander W Beham; Wolfgang E Kaminski; Michael Neumaier (PLoS ONE, 2018)
Recent evidence indicates the presence of macrophage subpopulations that express the TCRαβ in chronic inflammatory diseases such as tuberculosis and atherosclerosis and in the tumor microenvironment. Here, we demonstrate that a second subpopulation of macrophages expresses rearranged heavy and light chain immunoglobulins. We identify immunoglobulin expression in human and murine monocytes, in ex vivo differentiated macrophages and macrophages from the tumor microenvironment of five randomly selected distinct human tumor entities. The immunoglobulin heavy and light chains are expressed in a small macrophage subfraction (~3-5%) as combinatorial and individual-specific immune receptors. Using Sanger sequencing and deep sequencing, we routinely find markedly restricted Ig repertoires in monocytes/macrophages compared to normal B cells. Furthermore, we report the complete Ig heavy and light chain sequences of a fully functional immunoglobulin from a single tumor-associated macrophage. These results demonstrate that Ig expression is a defining feature of monocytes and also macrophages in the tumor microenvironment and thus reveal an as yet unrecognized modus operandi of host defense in professional phagocytes.